On the Continuity and Origin of Identity in Distributed Ledgers: Learning from Russell's Paradox. - Parra Moyano, JosÉ (Metaphilosophy, 2017)
This article studies the origin and continuity of the identity of the entities inscribed in a distributed ledger. Specifically, it focuses on the differences between the identities of the entities that exist in a distributed ledger and those of the entities that exist outside the ledger but must be represented in the ledger in order to interact with it. It suggests that a distributed ledger that contains representations of entities that exist outside the ledger can yield a continuum of interconnected existing and past identities that is constantly redefined to represent new conceptual entities. This continuum can be understood as a metasortal-or a sortal of sortals-that resembles the mathematical structure of a set of sets. Further, the article presents the dilemma that arises when representing the identities of entities in a distributed ledger, and it draws an analogy between this dilemma and Russell's Paradox.